Analisis Penetapan Biaya Produksi Dan Penentuan Harga Jual Iklan Pada PT Radio Suara Tiara Indah - Sonya Meiristia; Azli Fahrizal; Eka Sariningsih (Universitas Malahayati, 2017)
This study aimed to analyze the accuracy of PT Radio Suara Tiara Indah indetermining the cost of production and the selling price of the ad to the client, because theaccuracy of the management plan is very cost effect on earnings in PT Radio Suara TiaraIndah. This study used secondary data, documentation, participant observation, structuredinterviews, and library research and use descriptive method with qualitative approach. Theresults of this study showed that the cost of production and the selling price of the specifiedad less precise, because it is not done in accordance with existing methods. So it is difficult toknow whether the determination of the production cost and the selling price was right or not.